Tectonic context of the volcanic area of Purace and alkaline province of the upper Magdalena valley (2009)
It is well known that seismic activity allows the understanding of the region's geodynamic general characteristics. This paper analyses seismic events around Purace volcano and their relationship with the processes happening at the convergent margin between the South American and Nazca plates. The seismicity is randomly distributed beneath the continent and there are not enough events to properly define a Benioff Zone. The absence of seismicity at intermediate depth suggests that the subducting oceanic crust, is young and hot; therefore, it is less rigid and takes less time to be incorporated in the mantle. This is validated further by the recent volcanism in the upper Magdalena valley, where there are magmas with identifiable mantle input in their genesis. In the other hand, there are adakitic magmas in the Purace volcano which could be related to the presence of a paleo-ridge in the subducting plate underneath the SW of Colombia; this model also explains the alkaline province in the back-arc. The proposed hypothesis reconciles the thermal models with geochemical information and makes a significant contribution to the study of arc magmatism and the thermal evolution of convergent margins.